Beyond the Exodus: A Critical Review of "The Status of Youth in Agrifood Systems" - Komang Ariyanto (The Journal of Indonesia Sustainable Development Planning, 2026)
This review examines the book The Status of Youth in Agrifood Systems published by the Food and Agriculture Organization (FAO, 2025). The book shifts the common narrative that portrays youth as leaving agriculture toward a more nuanced perspective that highlights young people who actively participate in agrifood systems but face structural constraints. Rather than attributing declining youth engagement to lack of interest, the book emphasizes systemic barriers such as limited land access, financial constraints, labor market conditions, and institutional policies. This framing situates youth not as a problem but as strategic actors in sustainable agrifood transformation.